The power of existing buildings : save money, improve health, and reduce environmental impacts - Sroufe, Robert Paul; Stevenson, Craig (Craig E.); Eckenrode, Beth (Island Press, 2019)
"Your building has the potential to change the world. Existing buildings consume approximately 40 percent of the energy and emit nearly half of the carbon dioxide in the US each year. In recognition of the significant contribution of buildings to climate change, the idea of building green has become increasingly popular. But is it enough? If an energy-efficient building is new construction, it may take 10 to 80 years to overcome the climate change impacts of the building process. New buildings are sexy, but few realize the value in existing buildings and how easy it is to get to "zero energy" or low-energy consumption through deep energy retrofits. Existing buildings can and should be retrofit to reduce environmental impacts that contribute to climate change, while improving human health and productivity for building occupants. In The Power of Existing Buildings, academic sustainability expert Robert Sroufe, and construction and building experts Craig Stevenson and Beth Eckenrode, explain how to realize the potential of existing buildings and make them perform like new. This step-by-step guide will help readers to: understand where to start a project; develop financial models and realize costs savings; assemble an expert team; and align goals with numerous sustainability programs. The Power of Existing Buildings will challenge you to rethink spaces where people work and play, while determining how existing buildings can save the world. The insights and practical experience of Sroufe, Stevenson, and Eckenrode, along with the project case study examples, provide new insights on investing in existing buildings for building owners, engineers, occupants, architects, and real estate and construction professionals. The Power of Existing Buildings helps decision-makers move beyond incremental changes to holistic, results-oriented solutions"--Publisher's description